Diversity Of Fusarium Species In Peat Soils - Karim, Nurul Farah Abd (2013)
The occurrence and diversity of Fusarium species were determined from 23 peat soil samples collected from peat swamp forest, water-logged peat and peat soils from oil palm plantations. From soil analysis, the peat soils were mostly sandy and loamy sand, acidic (pH 3-4) with low nitrogen and carbon content and low moisture content. Based on the morphological characteristics of macroconidia, microconidia, conidiogenous cells, colony appearance and pigmentation, five Fusarium species were identified namely, F. oxysporum (60%), F. solani (23%), F. proliferatum (14%), F. semitectum (1%) and F. verticillioides (1%). These species are widely distributed worldwide and are common soil inhabitants which act as saprophyte and decomposer. Species identity was confirmed through DNA sequencing of translation elongation factor (TEF-1α). For species from Gibberella fujikuroi species complex, F. verticillioides and F. proliferatum, mating study was conducted. Mating study results showed that nine isolates of F. proliferatum and two isolates of F. verticillioides carried MAT 2 allele. Cross fertility test indicated that nine morphologically identified F. proliferatum were confirmed as F. proliferatum after cross-fertile with mating population D (Gibberella intermedia) and only one isolate was confirmed as F. verticillioides (Gibberella moniliforme) after cross-fertile with mating population A. From phylogenetic analysis using TEF-1α and β-tubulin genes based on individual dataset and combined dataset using neigbour-joining (NJ) and maximum likelihood (ML) methods, showed that the isolates from the same species were clustered in the same clade.